Impacto de la Pandemia de COVID-19 en la Práctica de la Neuromodulación en Argentina - Cremaschi, Fabián; Vázquez, Emmanuel Alejandro; Fausti, Renzo; Piedimonte, Fabián (Revista Argentina de Neurocirugía, 2021)
Background: The objective of this study was to evaluate the impact of the Covid-19 outbreak in the practice of Neuromodulation in Argentina. Methods: A survey was sent to Argentina neuromodulation practitioners from July 19 to August 20, 2020. The impact of Covid-19 on the professional and personal level were determined. All variables were compared and analyzed. Results: Twenty-four practitioners responded to the complete survey. Most of them were male (87.5%), in the 45-59 year age group (37.5%), with 15 or more years of experience (45.83%). Neurosurgeons were in the majority (87.5%), with ablative techniques being the predominant practice (26.47%). The great majority reported a decrease in surgical practices (83.33%), between 50 and 74% of them (40%), with the decision of the financer being the most cited reason (43.47%), and Deep Brain Stimulation the most affected surgical technique (41.6%). 100% of the interviewed declared that the patients had been harmed by the suspension of surgeries, and that the economic income was reduced in some way in 100% of the interviewed. On a personal level, none of the professionals reported having been diagnosed with the disease. However, 37.5% suffered physical manifestations, and 20.83% reported psychological sequelae, especially anxiety. Conclusion: The current Covid-19 pandemic yielded a significant impact on the daily work practice as well as on the personal level of practitioners in neuromodulation in Argentina. This impact must be taken into account in the long term to avoid further harmful effects and their sequels and to take appropriate preventive measures in the event of another pandemic.